1004 A Review of Over 300 Sentinel Lymph Node Biopsies, Is Magtrace Reliable?. (19th August 2022) - Khan, S; Wilson, RL; Shaker, H; Hobbs, N; Abbas, A; Absar, SM; Nasir, N; Wright, C; Williams, KE
Abstract: Introduction: With the ever-growing evolution of sentinal lymph node biopsy techniques, Magtrace was introduced to our department as a radiation free technique. This study aims to review the outcomes of Magtrace for SLNB. Method: Consecutive procedures invoking SLNB were conducted from 1st April 2020 to 29th July 2021. Retrospective data collection via theatre logs and patient notes was also performed. Results: 316 SLNB procedures were conducted during the above time period. In 197 (62.5%) procedures, Magtrace alone was used. Magtrace and blue dye was used in 104 (33%) procedures, radioisotope, and blue dye in 10 (3%) procedures, whilst radioisotope was used in 5 (1.5%). Overall, there were five (1.5%) failures of SLNB (i.e., axillary node sample was required), three with Magtrace and blue dye, two with Magtrace alone. Radioisotope was used as a precautionary measure when there was either a retroareolar magseed or multiple magseeds to guide the wide local excision. There were no reported adverse events following the injection of Magtrace. There was one anaphylaxis following injection of blue dye. One patient required postoperative MRI after Magtrace was used making interpretation more difficult. Conclusion: Magtrace outcomes are comparable to those reported for the traditional dual technique with blue dye and radioisotope and can be safely used as a single agent.